2016
DOI: 10.1016/j.spmi.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Simulation study of a new InGaN p-layer free Schottky based solar cell

Abstract: On the road towards next generation high efficiency solar cells, the ternary Indium Gallium Nitride (InGaN) alloy is a good passenger since it allows to cover the whole solar spectrum through the change in its Indium composition. The choice of the main structure of the InGaN solar cell is however crucial. Obtaining a high efficiency requires to improve the light absorption and the photogenerated carriers collection that depend on the layers parameters, including the Indium composition, p-and n-doping, device g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…This mathematically secured procedure is largely used in physical engineering areas such as mechanical, electrical, or civil engineering [7][8][9]. We have used this method for the design and the optimization of solar cells [10][11][12] and propose with this paper, to fully detail and completely release it and the software behind it for the free use of all, under the MIT License.…”
Section: Newton-based Optimization Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This mathematically secured procedure is largely used in physical engineering areas such as mechanical, electrical, or civil engineering [7][8][9]. We have used this method for the design and the optimization of solar cells [10][11][12] and propose with this paper, to fully detail and completely release it and the software behind it for the free use of all, under the MIT License.…”
Section: Newton-based Optimization Methodsmentioning
confidence: 99%
“…In this context, we used SLALOM to precisely seek the optimal efficiency that can be achieved by InGaN PN junction solar cells, using as-realistic-as-possible physical models with parameters extracted from experimental data, with the aim to simultaneously optimize the cell 5 following parameters : the Indium composition alongside the P and N layers dopings and thicknesses. These parameters and the used models have been detailed previously [10,11]. Table 1 and equation 2give the values that were taken for the bandgap, the affinity, the density of states, and the absorption.…”
Section: Optimization Of An Ingan Pn Junction Solar Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…For relatively high-Indiumcontent structures, Doolittle et al [5] theoretically showed that a p-i-n structure having an Indium composition of 60% exhibits * Corresponding author Email addresses: abdoulwahab.adaine@univ-lorraine.fr (Abdoulwahab Adaine), sidi.hamady@univ-lorraine.fr (Sidi Ould Saad Hamady), nicolas@fressengeas.net (Nicolas Fressengeas) a maximum efficiency of about 19%. Our previous studies [6,7] have shown that single junction structures have conversion efficiencies not exceeding 20%. The p-n structure presents an optimal efficiency of 17.8% while that of a p-i-n structure is 19.0%.…”
Section: Introductionmentioning
confidence: 99%
“…When the direct experimental data are not available, the InGaN parameters values are determined using Vegard's law linear interpolation between InN and GaN binaries values, except for the bandgap (E g ) and the electronic affinity (χ), where we used a quadratic modified Vegard's law with a bowing parameter of b = 1.43 eV for the bandgap and b = 0.8 eV for the electronic affinity [18]. All these physical models and dependent material parameters are detailed in our previous work [6,7] and summarized in table 1.…”
Section: Introductionmentioning
confidence: 99%